2017
DOI: 10.1186/s12904-017-0228-6
|View full text |Cite
|
Sign up to set email alerts
|

Path modeling of knowledge, attitude and practice toward palliative care consultation service among Taiwanese nursing staff: a cross-sectional study

Abstract: BackgroundThe Taiwanese government has promoted palliative care consultation services (PCCS) to support terminally ill patients in acute ward settings to receive palliative care since 2005. Such an intervention can enhance the quality of life and dignity of terminally ill patients. However, research focusing on the relationship between the knowledge, attitude and practice of a PCCS using path modelling in nursing staff is limited. Therefore, the aim of this study was to elucidate the effect of path modeling on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 23 publications
4
25
0
1
Order By: Relevance
“…The positive correlations among knowledge, attitude and self-efficacy presented in this study agreed with the ‘knowledge–attitude–practice’ theory 51 52. Knowing the correct knowledge about ageing is beneficial for caregivers to develop an optimistic attitude towards elderly people 51.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The positive correlations among knowledge, attitude and self-efficacy presented in this study agreed with the ‘knowledge–attitude–practice’ theory 51 52. Knowing the correct knowledge about ageing is beneficial for caregivers to develop an optimistic attitude towards elderly people 51.…”
Section: Discussionsupporting
confidence: 83%
“…Knowing the correct knowledge about ageing is beneficial for caregivers to develop an optimistic attitude towards elderly people 51. Accordingly, positive attitude is beneficial in improving people’s beliefs about their capabilities 52. Therefore, these closed associations indicated that an effective workforce management for caregivers should take knowledge, attitude and self-efficacy into account.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that nursing staff with a higher educational level would have better practice behaviors about the DNR signature. This nding was similar to a prior study that holders of a master's degree indirectly and positively in uenced good practice toward palliative care [20]. Higher educational levels among nurses meant having more con dence to deal with patients' problems in clinical nursing practices [37].…”
Section: Path Modeling Of Knowledge Attitude and Practicesupporting
confidence: 85%
“…Most prior studies indicate similar results. A study in Taiwan showed that a higher level of knowledge toward palliative care consultation service among nurses was associated with participation in education related to palliative care [20]. Having a bachelor of science or a higher degree in nursing, working in an Emergency department, having a daily experience of caring for chronically ill patients and taking part in a training on end of life care were signi cantly associated with good knowledge of nurses toward the end of life care [21].…”
Section: Factors Affecting the Kap-dnr Among Nursesmentioning
confidence: 99%
“…In hospital settings, palliative care and cancer care patient are often combined and occurred together [1,2]. As for palliative care nursing, patient care of knowledge and attitude are also commonly and often co-occurred with one another [3,4]. In many situations, it is very hard to observe the association of two or more symptoms at one moment.…”
Section: Introductionmentioning
confidence: 99%